(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
Horticultural greenbelts are an important source of local food for cities. Villa María and Villa Nueva are production centers that, in addition to conventional production, have agroecological productions. The construction of a community planter, within an agroecological horticultural establishment, provides a space for articulation and knowledge that contributes to the social fabric. The extension project allowed university students and residents of the town of Villa María to make visible the activities that are carried out in local food productions, understanding the importance and scope of the participatory actions carried out within the framework of the same.